Eight‐year results of the Spiesser study, a randomized trial comparing de novo sirolimus and cyclosporine in renal transplantation. (5th January 2016) - Gatault, Philippe; Bertrand, Dominique; Büchler, Matthias; Colosio, Charlotte; Hurault de Ligny, Bruno; Weestel, Pierre‐François; Rerolle, Jean‐Philippe; Thierry, Antoine; Sayegh, Johnny; Moulin, Bruno; Snanoudj, Renaud; Rivalan, Joseph; et al.
Summary: We present the results at 8 years of the Spiesser study, a randomized trial comparing de novo sirolimus and cyclosporine in kidney transplant recipients at low immunologic risk. We assessed estimated glomerular filtration (eGFR), graft, patient, and death‐censored graft survival (log‐rank compared), de novo DSA appearance, risk of malignancy, post‐transplant diabetes mellitus (PTDM), and anemia. Intent‐to‐treat and on‐treatment analyses were performed. Graft survival was similar in both groups (sirolimus: 73.3%, cyclosporine: 77.7, P  = 0.574). No difference was observed between treatment groups concerning patient survival ( P  = 0.508) and death‐censored graft survival ( P  = 0.858). In conditional intent‐to‐treat analysis, mean eGFR was greater in sirolimus than in cyclosporine group (62.5 ± 27.3 ml/min vs. 47.8 ± 17.1 ml/min, P  = 0.004), in particular because graft function was excellent in patients maintained under sirolimus (eGFR = 74.0 ml/min). Importantly, no detrimental impact was observed in patients in whom sirolimus has been withdrawn (eGFR = 49.5 ml/min). Overall, 17 patients showed de novo DSAs, with no difference between the two groups ( P  = 0.520). Malignancy did not differ by treatment. An initial maintenance regimen based on sirolimus provides a long‐term improvement in renal function for kidney transplant patients, especially for those maintained on sirolimus.